EXPLORING THE TRANSFORMATIVE EFFECT OF PROBLEM-BASED LEARNING MODELS IN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS ON STUDENTS' RATIONAL THINKING ABILITY ACROSS GENDER - Sholikhah, Khoirotus; Irawan, Edi; Wijaya, Tommy Tanu (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
The rational thinking abilities of students require development through effective learning strategies. This study investigates the effectiveness of a STEM-based Problem-Based Learning (PBL) model in enhancing students' rational thinking abilities, with consideration for gender differences. This research uses a quantitative approach and a quasi-experimental design. Data analysis involved the application of Two-Way ANOVA and Scheffe tests utilizing SPSS software. Participants consisted of Class VII students from MTs Ma'arif Balong Ponorogo. The findings indicate the following: (1) the initial rational thinking abilities of the experimental and control groups were comparable; (2) the STEM-based PBL model demonstrated superior effectiveness in improving students' rational thinking skills when compared to conventional learning methods; (3) no significant disparity in rational thinking abilities were observed between male and female students; (4) an interaction effect between the learning model and gender was detected, influencing students' rational thinking abilities. Specifically, female students displayed superior rational thinking abilities when exposed to the STEM-based PBL model. Conversely, no gender-based discrepancy in rational thinking abilities was observed among students utilizing the conventional model. These findings underscore the potential of the STEM-based PBL model as an alternative approach to foster students' rational thinking abilities.